PERANCANGAN TAMAN EDUKASI SEBAGAI UPAYA MENDUKUNG OUTDOOR LEARNING PROCESS DI SEKOLAH - Setyabudi, Irawan; Santoso, Dian Kartika; Istikomayanti, Yuswa (Aksen : Journal of Design and Creative Industry, 2022)
Architecture plays an important role in creating space for human activity. One form is an open space designed as a garden. Recently, the idea of caring for the environment has been implemented in schools with the Adiwiyata program by realizing school members who are responsible for environmental protection and management through school management to support sustainable development. The garden design process is environmentally friendly supporting facilities. The design case study was carried out at SMP 26 Malang. The problem is, the gardens around the main school in every corner or in front of the class have no thematic grouping of plant species, graffiti on the fence walls that need updating, no canopy for circulation, and many other elements that can be processed. The research method was carried out qualitatively with architectural design methods and adapted to education science. The purpose of this study is to provide a garden designconcept that is able to accommodate educational and recreational out-of-class activities for students of SMPN 26 Malang and can be generalized as a general design concept of an educational park for schools. Recommendations from the design are in the form of out-of-class learning concepts. The concept base that will be developed is from a smart and studentfriendly park which means that the park takes into account aspects of the intellectual, physical and psychological wellbeing of students, besides that it does not cause mental and physical harm. A participatory element in its implementation is needed. Keywords: Garden concept, outdoor learning process, smart-student friendly park